Repair of ultraviolet light-damaged deoxyribonucleic acid in sbc-A strains of Escherichia coli K-12. - Shlaes, D M (1979)
An Escherichia coli strain carrying both rec+ and sbcA has been constructed. Repair of ultraviolet light-induced deoxyribonucleic acid damage was examined by measuring survival and thymine-dimer excision in the rec+ sbcA strain as well as rec+ sbcA+ and recB recC sbcA strains. The sbcA mutation restores normal survival in both recB recC uvrB and recB recC uvr+ strains. Excision of thymine-containing dimers does not occur in uvrB mutants, regardless of the rec or sbcA genotype. Survival, after ultraviolet-light damage, of a rec+ sbcA strain is quantitatively similar to rec+ sbcA+ and recB recC sbcA strains.